About methods of diagnosing anomy in Alzheimer’s dementia - Antczak-Kujawin, Justyna (Interdyscyplinarne aspekty diagnozy i terapii logopedycznej, 2020)
About methods of diagnosing anomy in Alzheimer’s dementia In the dissertation, the term of naming disorder diagnosing concerning people suffering from Alzheimer’s disease has been described. The author’s proposals of anomie diagnosis methods that can be useful in speech therapy test of lexical and semantic skills in the elderly people have been presented. The procedure of speech disorders diagnosing during the process of senior disorders have been presented. Besides, the importance of lexical and semantic speech disorders in people suffering from Alzheimer’s disease has been emphasized. Moreover, aiming at explaining the mechanism of access to lexical scope and the process of names updating (searching), various models of language processing and mental lexicon organization have been thoroughly elaborated.